Limonadnica, odbiratelj in drugo slovensko komunikološko izrazje - Kalin Golob, Monika (Jezik in slovstvo, 2000)
In March this year, The Faculty of Social Sciences published the second volume of Communicological Chrestomathy, which brings seminal communicological texts of the first half of the 20th century. When the texts were being translated, it was suggested something ough to be done to provide for a more uniform Slovene communicological terminology. As a result, the Communicological Terminology was established at the Slovene Communicological Society in 1998. The section's first task is to coordinate, produce and suggest Slovene terms for the conceptual and material world of the science of communication, primarily on the basis of translating from English basic communicological literature for students of communicology.
Keywords: Slovene; slovenščina; communication sciences; komunikologija; terminologija; terminology